Outcomes of patients with disease recurrence after treatment for locally advanced non-small cell lung cancer detected by routine follow-up CT scans versus a symptom driven evaluation. (September 2019) - Bodor, J. Nicholas; Feliciano, Josephine L.; Edelman, Martin J.
Highlights: Largest experience to date of the results of follow-up testing stage III NSCLC. No survival difference between relapse detected by symptoms vs. routine CT chest. Favorable outcomes seen in symptomatic patients with only CNS relapse. The CNS results obscured potential benefits from chest CT. Routine CNS and chest imaging may improve outcomes. Abstract: Objectives: The majority of patients with locally advanced non-small cell lung cancer (LANSCLC) will recur after receiving multimodal treatment with curative intent. Current guidelines recommend routine follow-up with computerized tomography (CT) scans, though minimal data exist on the utility of this approach nor has an optimal follow-up strategy to detect recurrence been defined. This study examined whether survival varied if relapse was detected with scheduled follow-up CT versus symptoms, and whether the pattern of recurrence affected these outcomes. Materials and methods: Single institution retrospective review of patients who had undergone definitive management of LANSCLC with chemoradiotherapy +/- surgical resection. Standard follow-up testing consisted of routine exam and chest CT beginning at every 3 months in the first year and decreasing to annually after the fifth year. Results: 311 patients were assessed, of which 167 patients recurred and were evaluable. 104 progressions were detected by follow-up and 63 by symptoms. For the entire group, there was no difference in overall survival (OS) for those detected by scans vs. symptoms (7.6 vs. 6.1 months, p = 0.797). After excluding patients with oligometastatic (1–3) brain metastases (OBM), OS was superior in patients with scan detected relapse (7.5 vs. 3.4 months, p = 0.013). Conclusions: Routine surveillance by CT chest detects more localized disease than symptom driven follow-up, though OS does not differ. This null result is largely driven by the favorable outcomes for patients with OBM who present symptomatically. A strategy of both chest and brain imaging could be considered and warrants further investigation.